Exercise reduces pain and improves physical function for people awaiting hip replacement surgery - Henschke, Nicholas; Diong, Joanna (British journal of sports medicine, 2014)
Gill SD , McBurney H. Does exercise reduce pain and improve physical function before hip or knee replacement surgery? A systematic review and meta-analysis of randomised controlled trials. Arch Phys Med Rehabil 2013; 94 :164-76 - - Hip and knee replacement surgery can reduce pain and improve physical function in people with osteoarthritis.1 Interventions to improve or maintain physical function before surgery may improve postoperative outcomes,2 but only a small proportion of people receive such interventions before surgery3 and the effects of most preoperative exercise interventions remain uncertain.4 - - This systematic review aimed to determine whether preoperative exercise interventions can reduce pain and improve physical function before hip or knee joint replacement surgery. - - Four computer databases (CINAHL, MEDLINE, EMBASE and Cochrane Library) were searched up to July 2012 and reference lists of retrieved articles were screened. Titles and abstracts were screened by one reviewer for eligibility. - - Studies were eligible if the effect of preoperative exercise-based intervention compared to no intervention on pain and/or physical function was assessed in participants awaiting hip or knee replacement surgery using a randomised or quasi-randomised design, and the study …